Assessment of cross-flow filtration as microalgae harvesting technique prior to anaerobic digestion: Evaluation of biomass integrity and energy demand. (December 2018) - Giménez, Juan B.; Bouzas, Alberto; Carrere, Hélène; Steyer, Jean-Philippe; Ferrer, Jose; Seco, Aurora
Highlights: Cross-flow filtration (CFF) affected microalgae cell-wall integrity. Biodegradability of microalgae biomass was dependent on cell-wall integrity. Biomass solubilisation was related to a stress-induced release of organic polymers. A net energy demand was found for CFF regardless of the concentration achieved. Electricity demand was lower than heat demand for COD concentrations below 1% (w/v). Abstract: In the present study, the effect of cross-flow filtration (CFF) on the overall valorization of Chlorella spp. microalgae as biogas was assessed. The effect of CFF on microalgae cell integrity was quantified in terms of viability which was correlated with the anaerobic biodegradability. The viability dropped as the biomass concentration increased, whereas anaerobic biodegradability increased linearly with the viability reduction. It was hypothesized that a stress-induced release and further accumulation of organic polymers during CFF increased the flux resistance which promoted harsher shear-stress conditions. Furthermore, the volume reduction as the concentration increased entailed an increase in the specific energy supply to the biomass. The energy demand was positive in the whole range of concentrations studied, yielding an overall energy efficiency as high as 22.9% for the highest concentration studied. Specifically, heat requirements were lower than electricity requirements only when the biomass concentrations exceeded 10 g COD·L −1 .